Jurnal Hukum Agraria PENGARUH CATUR TERTIB PERTANAHAN DALAM PENDAFTARAN TANAH DI KOTA SINGKAWANG: Hukum Agraria - Nurzia, U. (Lembaga Marwah Rakyat, 2023)
In order to provide certainty of rights and legal certainty for the community, in accordance with Government Regulation Number 24 of 1997 concerning Land Registration, the government is required to register all land parcels in the territory of Indonesia, whether through systematic registration or sporadically. It is hoped that with the registration program, more and more people will be able to obtain certificates of land rights, so that in the future land administration will be better and orderly. As stated in the Order of Land Affairs, there are several things that will be realized in this program, including: orderly land law, orderly use of land, orderly maintenance and the environment and of course including orderly land administration as well. In the city of Singkawang, there has been a significant increase in the number of land parcels that have obtained certificates of land rights since the implementation of this program. Land problems that are always there, can also be eliminated or even eliminated, including disputes over the boundaries of land parcels due to unclear stakes and illegal (illegal) land tenure